Overview on current research status and development trends of hydrogen-powered rail transit - CHEN Weirong; WANG Yingmin; LI Bingxun; MENG Xiang; ZHANG Shicong; LI Qi (机车电传动)
Hydrogen fuel cells, boasting their technical features of cleanliness, environmental and high efficiency, have been gaining significant attention in response to the "carbon peaking and carbon neutrality" goals. In recent years, hydrogen-powered rail vehicles have achieved fruitful results as one of the effective approaches towards the low-carbon transformation and sustainable development in the rail sector. This paper began with an introduction to the current development status of hydrogen-powered rail transit at home and abroad. Then, the core technologies involved were expounded, including the integration and control of hydrogen fuel cell systems, energy management for hybrid power, and fault diagnosis and service life prediction of fuel cells, with a focus on their technical pros and cons and scopes of application. In addition, the existing issues and challenges were analyzed and the development orientations were raised according to the practical considerations. Finally, the development trends of hydrogen-powered rail transit were prospected from different perspectives to provide a reference for further development and application.